Intracellular expression of CD61 precedes surface expression - Käfer, Gabriele; Willer, Andreas; Ludwig, Wolf-Dieter; Krämer, Alwin; Hehlmann, Rüdiger; Hastka, Jan (Annals of hematology, 1999)
We report a case of acute myeloid leukemia which we have classified as acute megakaryoblastic leukemia because of intracytoplasmic expression of CD61. Light microscopy demonstrated agranular blasts which, by cytochemical staining, were negative for myeloperoxidase. Using flow cytometry, the blast cells were seen to be positive for HLA-DR, CD7, CD13, CD33, and CD34, thus revealing their myeloid origin. Immunophenotyping on fixed blood smears additionally showed positive reaction with the CD61 antibody, demonstrating the megakaryoblastic differentiation of the blasts. After permeabilization of the cell membrane, the intracytoplasmic CD61 expression was confirmed by flow cytometry. Cytogenetic analysis disclosed a del(7)(q21-22). Our findings suggest that cytoplasmic expression of CD61 may precede the cell-surface expression of this antigen and should therefore be investigated in all cases of acute leukemias with undifferentiated morphology and negative cytochemistry to set apart early FAB-M7 from FAB-M0.
Gesehen am 23.05.2022